Challenging Existing Perspectives of â€œIdealâ€ Characteristics of Teachers of English - Yeo, Marie; Marlina, Roby; Jacobs, George M (Beyond Words, 2017)
Addressing their concern about status inequalities among teachers of English, in this viewpoint paper, the authors argue that characteristics related to association with an Inner Circle country, Caucasian appearance, middle and upper class socio-economic status and university education seem to be related to the image of the â€œidealâ€ teacher of English to Speakers of Other Languages (ESOL). This image, in turn, affects job prospects, salary and recognition by students and peers. By reflecting on their experiences in relation to how well they fit the â€œidealâ€, the authors show that the construct is highly flawed and potentially destructive and divisive. To redress the inequities brought about by perceptions of the â€œidealâ€ language teacher, strategies pertaining to providing role models, raising awareness, providing tools and techniques for improving proficiency, and discussing status and identity issues are suggested for assigning competence to people who do not fit the idealized image. The article aims to offer a fairly new perspective from the unique experiences of three established language teachers, one from each of Kachruâ€™s (1992) circles, and to also raise awareness about the need to accept greater diversity among language teaching professionals. Keywords: teacher identity, teacher characteristics, teacher employment, NNESTs, non-native teachers of English, assigning competence, narrative enquiry